Comparative Metagenomics Reveals Microbial Diversity and Biogeochemical Drivers in Deep-Sea Sediments of the Marcus-Wake and Magellan Seamounts - Chengcheng Li; Bailin Cong; Wenquan Zhang; Tong Lu; Ning Guo; Linlin Zhao; Zhaohui Zhang; Shenghao Liu (Microorganisms)
Seamounts are distributed globally across the oceans and are generally considered oases of biomass abundance as well as hotspots of species richness. Diverse microbial communities are essential for biogeochemical cycling, yet their functional partitioning among seamounts with geographic features remains poorly investigated. Through metagenomic sequencing and genome-resolved analysis, we revealed that Proteobacteria (33.18–40.35%) dominated the bacterial communities, while Thaumarchaeota (5.98–10.86%) were the predominant archaea. Metagenome-assembled genomes uncovered 117 medium-quality genomes, 81.91% of which lacked species-level annotation, highlighting uncultured diversity. In the Nazuna seamount, which is located in the Marcus-Wake seamount region, microbiomes exhibited heightened autotrophic potential via the 3-hydroxypropionate cycle and dissimilatory nitrate reduction, whereas in the Magellan seamounts regions, nitrification and organic nitrogen metabolism were prioritized. Sulfur oxidation genes dominated Nazuna seamount microbes, with 33 MAGs coupling denitrification to sulfur redox pathways. Metal resistance genes for tellurium, mercury, and copper were prevalent, alongside habitat-specific iron transport systems. Cross-feeding interactions mediated by manganese, reduced ferredoxin, and sulfur–metal integration suggested adaptive detoxification strategies. This study elucidates how deep-sea microbes partition metabolic roles and evolve metal resilience mechanisms across geographical niches. It also supports the view that microbial community structure and metabolic function across seamount regions are likely influenced by the geomorphological features of the seamounts.